Conceptual representation of digital medical images: Integrating Context and Visual Content - Roa Martínez, Sandra Milena; Borsetti Gregorio Vido, Silvana Aparecida; Vicentini Jorente, María José (Revista General de Información y Documentación, 2016)
This paper presented a proposal conceptual framework to represent digital medical images, which is integrated: 1) descriptive elements from the rules of cataloging and metadata standards for information resources, 2) standard for digital imaging and communications in medicine (DICOM) and 3) visual content of images provided by feature extraction techniques. We using the framework of functional requirements for bibliographic records (FRBR), the model of requirements functional for digital image data (RFDID) and model Entity- Relation (ER) to define and build the concepts embodied in the diagram proposed by this work, which integrates context information and visual content of a digital medical imaging for representation as an informational resource addressing the complexity of such images..